Relationship between level of income and method of contribution and appointment of Islamic Waqf Bank as an agent in collecting waqf fund / Muhammad Ridhwan Ab. Aziz ... [et al.] - Ab. Aziz, Muhammad Ridhwan; Yusof, Mohd Asyraf; Johari, Fuadah; Sabri, Hisham (Faculty of Business and Management, 2014)
Receiving a good education helps empower people knowledge, thus making them strong enough to look after themselves in any given situation. It keeps oneself aware of given surrounding as well as the rules and regulations of the society they living in.